DAMPAK MEDIA SOSIAL TIKTOK PADA PENURUNAN PRESTASI BELAJAR SISWA KELAS XI SMA NEGERI 19 KABUPATEN TANGERANG - Salsabila Rahmatika; Bangun Yoga Wibowo; Lenny Wahyuningsih (STKIP Subang, 2026)
This study aims to determine whether the use of TikTok on learning achievement of eleventh-grade students at SMA Negeri 19, Tangerang Regency. The method used is a quantitative approach with correlational techniques. A total of 80 eleventh-grade students, representing the entire population, were sampled using a saturated sampling technique. The overall analysis revealed an average score for variable X of 141.88, out of a maximum ideal score of 192, equivalent to a high achievement of 73.90%. The average score for variable Y was 141.84, out of a maximum ideal score of 192, equivalent to a high achievement of 73.88%.